Survey of Real-Time Communication in CSMA-Based Networks - Ricardo Moraes (2010)
The purpose of this paper is to survey the state-of-the-art on real-time (RT) communication in CSMA-based networks and to identify the most suitable approaches to deal with the requirements imposed by next generation communication environments. The paper focuses in the two of the most relevant solutions that operate in shared broadcast environments, according to the CSMA medium access protocol (IEEE 802.3/802.11). RT communication solutions are classified according to two classification axes. The first axis is related to how collisions are dealt with. A second classification axis is related to the compatibility degree achieved by each of the proposed approaches. Finally, a RT communication framework that is adequate to support RT communication in shared environments is briefly discussed.